Colonization is Opposed to Freedom: Anti-Dutch Memories and the Didactic Practice of Indonesian History Teachers - Purnomo, Arif; Kurniawan, Ganda Febri; Em, Sereyrath; Mulianingsih, Ferani (Paramita: Historical Studies Journal, 2024)
This research examines the complexity of anti-Dutch memory in Indonesia by focusing on the idea that colonization is opposed to freedom. This research was carried out using qualitative methods. Data was collected using interview techniques, observation, and document study. The collected data was analyzed using a thematic analysis approach. An in-depth analytical exploration reveals how Dutch colonialism practices limited freedom. The concept of freedom in the context of colonialism includes restrictions on human rights, detrimental economic systems, and oppression of local culture. Anti-Dutch memory records persistent resistance through rebellion and war as a manifestation of freedom. The idea of independence was reflected in the Proclamation of Indonesian Independence in 1945, and liberator figures such as Soekarno became symbols of the struggle against colonialism. Anti-Dutch memory plays a central role in forming Indonesian national identity, constructing collective memory as a cultural heritage passed down through generations. This analysis enriches historical and social understanding, shows the complexity of teaching history, and emphasizes the importance of a contextual approach. This analytical exploration guides reflection on general statements and provides a basis for a deeper understanding of how essential freedom was in the struggle against colonialism. This article contributes to the Indonesian history education research literature. It opens space for further discussion about the impact of anti-Dutch memory on national identity and actual freedom in Indonesia.Penelitian ini mengkaji kompleksitas memori anti-Belanda di Indonesia dengan berfokus pada gagasan bahwa penjajahan bertentangan dengan kebebasan. Penelitian ini dilakukan dengan menggunakan metode kualitatif. Data dikumpulkan dengan menggunakan teknik wawancara, observasi, dan studi dokumen. Data yang terkumpul dianalisis dengan menggunakan pendekatan analisis tematik. Eksplorasi analitis mendalam mengungkap bagaimana kolonialisme Belanda mempraktikkan kebebasan yang terbatas. Konsep kebebasan dalam konteks kolonialisme mencakup pembatasan hak asasi manusia, merugikan sistem ekonomi, dan penindasan terhadap budaya lokal. Memori anti-Belanda mencatat perlawanan yang gigih melalui pemberontakan dan perang sebagai wujud kebebasan. Ide kemerdekaan tercermin dalam Proklamasi Kemerdekaan Indonesia tahun 1945, dan tokoh pembebas seperti Soekarno menjadi simbol perjuangan melawan kolonialisme. Memori anti-Belanda berperan sentral dalam pembentukan jati diri bangsa Indonesia, mengkonstruksi memori kolektif sebagai warisan budaya yang diwariskan secara turun-temurun. Analisis ini memperkaya pemahaman sejarah dan sosial, menunjukkan kompleksitas pengajaran sejarah, dan menekankan pentingnya pendekatan kontekstual. Eksplorasi analitis ini memandu refleksi atas pernyataan-pernyataan umum dan memberikan dasar untuk pemahaman yang lebih mendalam tentang betapa pentingnya kebebasan dalam perjuangan melawan kolonialisme. Artikel ini berkontribusi pada literatur penelitian pendidikan sejarah Indonesia. Hal ini membuka ruang untuk diskusi lebih lanjut mengenai dampak memori anti-Belanda terhadap identitas nasional dan kebebasan aktual di Indonesia.